Analysis of the Effect of Inflation, Open Unemployment Rate, and Poverty on Economic Growth in Bengkulu Province - Ariska Panjaitan; Merri Anitasari (Fakultas Ekonomi Dan Bisnis, Universitas Bengkulu, 2023)
This study aimed to investigate the impact of inflation, open unemployment rate, and poverty on economic growth in Bengkulu. For this study, time series data from 2010 to 2022 are used. The dependent variable in this study is economic growth. The independent variables used are inflation, the open unemployment rate, and poverty. This study uses multiple linear regression analysis methods. The results of this study indicate that the open unemployment rate variable has a significant positive effect on economic growth, and poverty has a significant negative effect on economic growth. While the inflation variable has an insignificant effect on economic growth in Bengkulu Province.